Investment Decisions, Funding Decisions On Company Value: Intervened by Profitability - Eldiana, Nora Aprilia; Sari, Desi Permata; Wijaya, Ronni Andri (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
This research aims to examine the influence of investment decisions and funding decisions on company value with profitability as an intervening variable in primary sector companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The sample selection technique used purposive sampling to obtain 32 primary companies. The data analysis technique uses multiple regression analysis and path analysis using SPSS 26. Based on the results of the hypothesis, partial investment decisions have no significant effect on profitability, partial funding decisions have a significant effect on profitability, partial investment decisions have no significant effect on company value, partial funding decisions have no significant effect on company value, partial profitability has a significant effect on company value, investment decisions have a significant effect on company value through profitability as an intervening variable, funding decisions have a significant effect on company value through profitability as an intervening variable in primary sector companies, Consumer Non-Cylicals. registered on the IDX 2019-2023.